Allelic relationship among genes for resistance to spot blotch (Bipolaris sorokiniana) in spring wheat - KULDEEP TYAGI, PRASHANT GOEL*, SWATI and (Indian Phytopathology, 2008)
Spot blotch caused by Bipolaris sorokiniana has become a major constraint in wheat production in tropics and subtropics, where mean temperature in the coolest months is above 17.5Â°C. All the F1 progenies showed resistant type of response towards spot blotch; however, segregation in the F2 generations revealed that resistant parents had a different set of genes conferring spot blotch resistance. Two crosses namely, PBW 373/PBW 343 and PBW 343/WH 581 segregated in the pattern of 15 (resistant):1 (susceptible) indicating that resistance to spot blotch is controlled by two dominant genes and the genes interacted with each other in duplicate manner. While, PBW 373/WH 581 gave a ratio of 9:7 (resistant/susceptible) indicating the complementary gene action. BC1 populations segregated in 3:1 (resistant/susceptible) ratio, which again confirmed the results of F2 generations.